The Use of Subbottom Profiling in Refining Dredge Cuts for a Large‐Scale Sediment Remediation Project. Issue 2 (March 2017) - Coles, Jill; Graham, Matthew; Riggs, Brian
Abstract : A number of different techniques were employed to locate the target dredge grade on a large‐scale Canadian sediment remediation project. These techniques included various coring events, Seabed Terminal Impact Newton Gradiometer (STING) testing, and geotechnical borings. Despite these techniques, the data set for interpolation of the dredge grade was widely spaced, and some of the investigations were not specifically intended to be used for defining the dredge grade. In order to reduce the risk of extra expenses from contractor claims resulting from differing sediment conditions, more precise planning was required. Due to the size of the area and the desired accuracy, subbottom profiling was identified as a potential tool to provide high‐density coverage across the site. As with any geophysical tool, ground truth data were required to verify and aid in interpretation. This article describes how subbottom profiling was used to refine the dredge grade for the target layer, the associated challenges related to signal loss in some areas, and how they were overcome. ©2017 Wiley Periodicals, Inc.